2022
DOI: 10.3390/life12111942
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Isolation Methods for Plasma-Derived Extracellular Vesicles in Patients with Hyperlipidemia

Abstract: Extracellular vesicles are commonly found in human body fluids and can reflect current physiological conditions of human body and act as biomarkers of disease. The quality of isolated extracellular vesicles facilitates the early diagnosis of various diseases accompanied by hyperlipidemia. Nonetheless, there are no reports on which special methods are suitable for isolating extracellular vesicles from the plasma of patients with hyperlipidemia. Thus, this study compared three different research-based extracellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…For the frozen sample data (n = 6), the 70 nm results of the comparison of the two types of columns were used. Based on our previous comparison of the 35 nm and 70 nm columns, which showed more efficient sEV isolation with less lipoprotein contamination in the 70 nm column, we isolated EVs collecting fractions 1-8 using the 70 nm column for this comparison [51].…”
Section: Characterisation Of Sevs Separated By An Sec 70 Nm Column Bo...mentioning
confidence: 99%
“…For the frozen sample data (n = 6), the 70 nm results of the comparison of the two types of columns were used. Based on our previous comparison of the 35 nm and 70 nm columns, which showed more efficient sEV isolation with less lipoprotein contamination in the 70 nm column, we isolated EVs collecting fractions 1-8 using the 70 nm column for this comparison [51].…”
Section: Characterisation Of Sevs Separated By An Sec 70 Nm Column Bo...mentioning
confidence: 99%
“…Several comparative studies suggested that purification methods affect yield, population, and the therapeutic efficacy of sEVs [ 124 , 125 , 126 , 127 , 128 ]. A position paper from the International Society for Extracellular Vesicles categorized the purification methods of sEVs in terms of point of recovery and specificity [ 6 ].…”
Section: Large-scale Expansion Of Cell Sources For Anti-cancer Sev Pr...mentioning
confidence: 99%